Pengelolaan Keuangan BAZNAS Kota Padang Panjang - Asrida Asrida; Arifandi Arifandi; Delvi Susanti; Atika Amor (ZAWA: Management of Zakat and Waqf Journal, 2024)
This research aims to determine the form of financial management of BAZNAS Padang Panjang City. This research was motivated by BAZNAS Padang Panjang City obtaining a WTP Opinion from the Public Accounting Office eight times in a row starting from 2016- 2023. The type of research that the author uses is field research with a qualitative approach. The research results show that the financial management of BAZNAS Padang Panjang City refers to PERBAZNAS Number 5 of 2018 which consists of budgeting, receiving funds, storing funds, spending funds, bookkeeping and archiving, and controlling. Overall financial management is very good, with effective planning, neat recording and adequate reporting, as proven by obtaining an Unqualified Opinion (WTP) from a public accounting firm and having implemented the applicable accounting system